Από την κοίτη του Αράχθου ως τα σκαλιά της εκκλησίας … Νέες επιγραφές από την Αμβρακία - Παπαδοπούλου Βαρβάρα N.; Γαλάνη Βασιλική (Tekmeria, 2025)
This article presents new votive and funerary inscriptions discovered in the city of Arta and its wider region, which relate to the ancient city-state of Ambracia. The finds include funerary stelae from the Arachthos riverbed, inscriptions from Hanopoulo and Koronisia recording religious officials (aozos, mageiros, oinochoos), a dedicatory inscription to Athena found near the Small Theatre-Bouleuterion, and reused inscriptions in Byzantine churches. The chronology of most inscriptions falls within the Hellenistic period (3rd - 2nd century BCE), with some extending to Roman times. Through the personal names and public offices they record, these inscriptions expand our prosopography of Ambracia and provide valuable insights into the city’s political structures, religious practices, and social organization. Notable findings include evidence of citizens from other Greek regions settling in Ambracia and new attestations of religious functionaries participating in civic cult activities.